Halquinol and nanoencapsulated essential oils: A comparative study on growth performance, intestinal morphology and meat quality in broiler chickens - Mendoza-Ordoñez, Gilmar (2023)
Diets supplemented with halquinol and/or nanoencapsulated essential oils (N-EOs) have shown positive effects on the productive parameters of broiler chickens. However, there is limited comparative evidence between these two products. This study aimed to investigate and compare the efficacy of N-EOs blends with halquinol as dietary supplements for broiler chickens. A total of 500 male Cobb 500 broiler chickens were randomly assigned to five dietary groups. The control group received a conventional diet supplemented with halquinol (60%), while the experimental groups received supplementation with N-EOs blends derived from soursop (S), lemon (L), and eucalyptus (E) in different proportions: T1 (S:33.33%, L:33.33%, E:33.33%), T2 (S:50%, L:25%, E:25%), T3 (S:25%, L:50%, E:25%), and T4 (S:25%, L:25%, E:50%). The trial lasted for 42 days. The results showed that the T1 and T4 groups obtained the highest values (p < 0.05) for average daily growth rate and breast yield. The feed conversion ratio was significantly lower in groups T1 and T4 (p < 0.05). All N-EOs supplemented groups exhibited higher carcass yield (p < 0.05). At day 42, the T1 group displayed increased villus height and villus height/crypt depth ratio in the duodenum (p < 0.01), while all experimental groups showed increased villus width in the jejunum and ileum (p < 0.05). Texture analysis revealed that N-EOs-treated groups had texture values similar to halquinol, except for the T1 group, which significantly increased hardness (p < 0.05). Bromatological analysis showed that the T4 group significantly improved the percentage of crude protein, fat, and ash compared to the halquinol-supplemented group (p < 0.05). Additionally, the T1 and T4 groups exhibited lower levels of lipid peroxidation (p < 0.05). In conclusion, dietary supplementation with N-EOs holds promise as a potential alternative to halquinol, with the added advantage of improved oxidative stability.